The Effects of Critical Multiliteracy Learning Models on Mastery of Explanatory Text Concepts - Dadan Setiawan; Tatat Hartati; Rahman Rahman; Isah Cahyani (International Journal of Science and Applied Science: Conference Series, 2019)
The aims of this study was to determine the ability to master the concept of elementary school students through the implementation of critical multiliteracy learning models. This research was conducted on fifth grade students of elementary school. The research method used in this study was a quasi-experimental method. The participants in this study amounted to 39 students. Data was collected using tests and rubric. Analysis of data in this research using the t test with SPSS version 20.0 program for windows. Based on the results of the study, it was found that the mastery ability of the explanatory text concept of students experienced a significant increase and was included in the sufficient category. This can be seen from the pretest score obtained by students at 34.74 and the posttest results at 64.23. Based on the results of the t test the significance value is 0.00˂0.05 thus it can be concluded that there are significant differences between the mastery of students' concepts before and after being given treatment using critical multiliteracy learning models.